Overview of Stigma and Community Attitudes Towards the Development of Android-Based Mental Health Intervention Media in Addressing the Issue of Community Stigma Towards People with Mental Disorders - Nauli, Fathra Annis; Sari, Tesha Hestiana; Azni, Anisa Yulvi; Sari, Dita Kartika (GLOBAL HEALTH SCIENCE GROUP, 2024)
Stigma towards People with Mental Disorders (ODGJ) is a serious problem in Indonesia. One of the efforts to address stigma against ODGJ involves promotional and preventive activities as part of a psychosocial approach, as outlined in Law No. 18 of 2014 on Mental Health. One of its goals is to eliminate stigma, discrimination, and human rights violations against people with mental disorders (ODGJ). In the digital era, android smartphones serve as communication tools and easily accessible sources of information due to their time, effort, and cost efficiency. The purpose of this research is to understand community attitudes towards the development of Android-Based Mental Health Intervention Media in addressing community stigma towards People with Mental Disorders (ODGJ) and to assess the stigma present in society towards ODGJ. This research is a descriptive quantitative study using purposive sampling on 100 community respondents. The study was conducted by distributing questionnaires on community attitudes towards the development of intervention media and questionnaires to assess community stigma towards ODGJ. The data was analysed descriptively and analytically. The results showed that the majority of the community stigma towards ODGJ remains low, at 59% (59 respondents), and community attitudes towards the development of intervention media applications are positive, at 62% (62 respondents). It is recommended that, with the positive attitude of the community towards the development of educational media to combat stigma against ODGJ, it can further reduce societal stigma towards ODGJ.